Enhancing optoelectronic properties of SiC-grown graphene by a surface layer of colloidal quantum dots - Makarovsky, Oleg; Turyanska, Lyudmila; Mori, N.; Greenaway, Mark; Eaves, Laurence; Patanè, Amalia; Fromhold, Mark; Lara-Avila, Samuel; Kubatkin, Sergey; Yakimova, Rositsa (IOP Publishing, 2017)
We report a simultaneous increase of carrier concentration, mobility and photoresponsivity when SiC-grown graphene is decorated with a surface layer of colloidal PbS quantum dots, which act as electron donors. The charge on the ionised dots is spatially correlated with defect charges on the SiC-graphene interface, thus enhancing both electron carrier density and mobility. This charge-correlation model is supported by Monte Carlo simulations of electron transport and used to explain the unexpected 3-fold increase of mobility with increasing electron density. The enhanced carrier concentration and mobility give rise to Shubnikov-de Haas oscillations in the magnetoresistance, which provide an estimate of the electron cyclotron mass in graphene at high densities and Fermi energies up to 1.2 × 1013 cm-2 and 400 meV, respectively.